Comparative Analysis of Economic Fiqh in Islamic Financial Transactions: ‎A Review of Literature from Various Madhhabs - Ghozali, Mohamad; Jubaedah, Dedah; Yusup, Deni Kamaludin (IAIN Syekh Nurjati Cirebon, 2024)
This study analyzes the comparative interpretations of Islamic economic jurisprudence (fiqh) in financial transactions across the Hanafi, Maliki, Shafi'i, and Hanbali schools of thought. Employing a descriptive qualitative approach, data were collected from academic literature, official documents, historical sources, and expert interviews. The research focuses on key Sharia financial transactions, including murabahah, mudarabah, musyarakah, ijarah, and sukuk, to explore the diversity of fiqh interpretations. The findings reveal significant differences, with the Hanafi and Maliki madhhabs showing greater flexibility and adaptability to socio-economic contexts, while the Shafi'i and Hanbali madhhabs maintain a stricter adherence to religious texts. These differences impact the design and implementation of Sharia-compliant financial products, influencing how they align with diverse fiqh perspectives. This study concludes that such variations highlight the dynamic and adaptable nature of Islamic economic jurisprudence in addressing diverse socio-economic needs. It underscores the importance of harmonizing interpretations to support the globalization of Islamic finance, ensuring inclusivity and sustainability without compromising Sharia principles. This research provides valuable insights into the role of madhhab diversity in shaping the growth and development of Sharia-compliant financial systems.Keywords: Economic Fiqh, Islamic Financial Transactions, Madhhab Comparison, Sharia Finance.